Intestinal microbial communities and Holdemanella isolated from HIV+/− men who have sex with men increase frequencies of lamina propria CCR5+ CD4+ T cells. (1st January 2021) - Yamada, Eiko; Martin, Casey G.; Moreno-Huizar, Nancy; Fouquier, Jennifer; Neff, C. Preston; Coleman, Sara L.; Schneider, Jennifer M.; Huber, Jonathan; Nusbacher, Nichole M.; McCarter, Martin; Campbell, Thomas B.; Lozupone, Catherine A.; et al.
ABSTRACT: Men who have sex with men (MSM), regardless of HIV infection status, have an intestinal microbiome that is compositionally distinct from men who have sex with women (MSW) and women. We recently showed HIV-negative MSM have elevated levels of intestinal CD4 + T cells expressing CCR5, a critical co-receptor for HIV. Whether elevated expression of CCR5 is driven by the altered gut microbiome composition in MSM has not been explored. Here we used in vitro stimulation of gut Lamina Propria Mononuclear Cells (LPMCs) with whole intact microbial cells isolated from stool to demonstrate that fecal bacterial communities (FBCs) from HIV-positive/negative MSM induced higher frequencies of CCR5 + CD4 + T cells compared to FBCs from HIV-negative MSW and women. To identify potential microbial drivers, we related the frequency of CCR5 + CD4 + T cells to the abundance of individual microbial taxa in rectal biopsy of HIV-positive/negative MSM and controls, and Holdemanella biformis was strongly associated with increased frequency of CCR5 + CD4 + T cells. We used in vitro stimulation of gut LPMCs with the type strain of H. biformis, a second strain of H. biformis and an isolate of the closely related Holdemanella porci, cultured from either a HIV-positive or a HIV-negative MSM stool. H. porci elevated the frequency of both CCR5 + CD4 + T cells and the ratio of TNF-α/IL-10 Genomic comparisons of the 3 Holdemanella isolates revealed unique cell wall and capsular components, which may be responsible for their differences in immunogenicity. These findings describe a novel mechanism potentially linking intestinal dysbiosis in MSM to HIV transmission and mucosal pathogenesis.